RESERVE SYSTEM TO IMPROVE LOGISTICS OF EMPTY CONTAINERS: CASE STUDY OF A CONTAINER STORE IN PERU - Chong, Mario Gustavo (2018)
The need to optimize the operational process of a warehouse for export container shipment motivated the present study. The scope has three objectives that focus on the shipment of empty reefer containers: first, to minimize shipment time, which currently takes an average of three hours, since the customer's transport enters the warehouse, receives the container and withdraws it; secondly, to improve the quality of the delivery state of the containers; and, third, to achieve a reduction in the operational costs of the shipment process.